PENGARUH PEMUPUKAN DAN PEMANGKASAN TERHADAP PERTUMBUHAN, STATUS HARA, DAN PRODUKTIVITAS TANAMAN HANDEULEUM (Graphtophyllum pictum (L) Griff.) - MUHAMAD DJAZULI; RATNA FATHAN (Pusat Penelitian dan Pengembangan Perkebunan, 1999)
Effect offertilizer and pruning on growth, nutrient status, and productivity of caricature plant (Graphtophyllum pictum (L) Grif.)Information on the effect of fertilizer and top cutting application on growth, nutient uptake, and productivity of caricatue plant (Graphtophyllum pictum (L) GrifT.) was limited. Increasing demand for that crop in the future as traditional medicine should be back up by applicable agronomical informations of caicature plant. The objective of this study was to evaluate the effect of fertilizer and pruning applications on growth, nutrient uptake, and productivity of caricature plant. The pot trial was conducted at the Research Institute for Spices and Medicinal Crops from August 1997 to January 1998. A randomized block design was arranged with two factors and 3 replications. Each treatment consisted of 5 plants. The irst factor consisted of three shoot cutting periods . (I) control; (2) 2 months ater planting (MAP) and (3) 4 MAP. The second factor was 6 fertilizer combinations: (1)-N, -P, -K, and manue (M); (2) -N, +P +K. and +M; (3) . +N, -P, +K, and +M; (4) +N, +P, -K, and +M; (5) +N, +P, +K, and -M; (6) +N, +P, +K, and +M, respectively. It was consideed that there were significant interaction between fertilizer and pruning applications, especially on the gowth and productivity of caricatue plant. Application of NPK and manue impoved plant productivity and nutrient status. Pruning treatments wee able to increase leaves fresh weight signiicantly. The highest productivity of caicatue plant was found at the combination teatment of pruning and N, K, Manue fertilizer applications. Theefore, the optimal growth and productivity could be achieved by early pruning and fertilizer application, especially manure.